A mixed methods exploration of talent development in team sports in Ireland: The role of the coaches - Sherwin, I.; Campbell, M. J.; MacIntyre, T. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
The development of talent in sport is located in the important relationship of athlete and coach (Coté et al., 2013). The current study aimed to investigate the talent development systems in team sports from a coaching perspective. By surveying expert coaches, we sought to establish their educational and athletic experience. The data collection procedure was a retrospective interview process and mirrored that proposed by Coté et al. (2005).This process focused on the "recall of factual knowledge about concrete activities they engaged in throughout their development (pp.4)" and was designed to collect information that could be verified by external sources. Methods: Male coaches from three team sports completed the survey. Inclusion criteria for coaches were defined as those with at least 10 years` experience coaching their sport and currently coaching more than four hours per week. Consequently, 20 respondents were invited to attend a follow-up semi-structured interview. Results: Participation in a diverse range of sports at an early age prior to specialisation in one sport through their teenage years was commonly reported. Typically, the initial introduction to coaching coincided with a highly competitive phase of their playing career. Their involvement in part-time coaching increased in their late 20s as their highly competitive participation decreased. Phenomenological experience was reported to be a contributor to learning in coaches. Our findings suggest that the coaches were highly educated with some specialisation in sport or physical education related disciplines. Additionally a minimum level of sport experience playing or coaching sports other than their primary sport, interaction with a mentor coach and some leadership role during the coach`s playing career contributed to the development process. Discussion: Criterion level experiences were deemed necessary but not sufficient to progress to high performance coaching. The attainment of these experiences did not guarantee progression to a high performance coaching level nor did it ensure success at any level. Further research is needed to gain a deeper understanding of the development of high performance coaches while some of the practical issues may be utilised to shape future coaching courses.